A QUALITATIVE FEASIBILITY STUDY TO INFORM FLUIDS IN SHOCK (FISH) – A PILOT RANDOMISED CONTROLLED TRIAL OF FLUID BOLUS THERAPY IN SEPTIC SHOCK. Issue 12 (18th November 2016) - O'Hara, C; Woolfall, K; Canter, R; Mouncey, P; Rowan, K; Lyttle, M; Peters, M; Inwald, D; Nadel, S
Abstract : Objectives & Background: There is increasing evidence that fluid overload may be associated with harm in paediatric critical illness. Fluids in Shock (FiSH) is a combined feasibility and pilot randomised controlled trial (RCT) to determine if restrictive fluid bolus therapy (10 ml/kg) is more beneficial than current recommended fluid bolus therapy (20 ml/kg) in the resuscitation of children with presumed septic shock. This qualitative feasibility study aims to explore: acceptability of the proposed pilot RCT, including the prospect of research without prior consent (RWPC); other potential barriers to conduct of the pilot RCT; participant information; parental decision-making; and patient-centred outcome measures. Methods: Qualitative interview study involving 21 parents (18 mothers, 3 fathers, 7 were bereaved) with children admitted to a UK emergency department with presumed septic shock in the last three years. Results: All parents would have provided permission for the use of their child's data in the FiSh pilot RCT. The majority of parents were unfamiliar with RWPC, yet supported its use in FiSh and in other RCTs aiming to help improve treatments for critically ill children. Parents were concerned about the change from currently recommended treatment; yet were reassured by an explanation of the current evidence base, fluid bolus therapy and monitoring procedures. Parents made recommendations about the timing of the discussion regarding permission for use of data and the patient information materials. Bereaved parents stated that recruiters should not attempt to discuss the RCT immediately after a child's death, but supported a personalised postal 'opt out' approach to RWPC for FiSh. Parents prioritised outcome measures such as survival, time in hospital, time spent on machines and time to their child 'looking or behaving more like themselves'. Conclusion: Our qualitative feasibility study findings support the proposed FiSh pilot RCT, including the use of RWPC, amongst parents whose child has experienced septic shock. Our findings will inform the FiSh RCT including selection of a patient centred outcome measure, as well as inform development of participant information materials and site initiation training.